Effect of Employment Status on the Association Among Sleep, Care Burden, and Negative Affect in Family Caregivers. (November 2021) - Ryuno, Hirochika; Yamaguchi, Yuko; Greiner, Chieko
Objective: To examine the effect of employment status on sleep, care burden, and negative affect among family caregivers (FCs) at home. Methods: An intensive longitudinal design was applied in which 25 FCs underwent in-home assessments for up to 56 days. At baseline, demographic data and employment status were collected. FCs wore a wrist-worn device with an accelerometer to assess objective total sleep time (TST) for consecutive 24-hour periods. FCs answered the Zarit Burden Interview (ZBI) and Positive and Negative Affect Schedule (PANAS) every night before sleep. Linear mixed model analysis was used to examine the effect of objective sleep status on ZBI and PANAS scores the following day. Results: Mean participant age was 66.3 ± 10.8 years (72.0% female), and mean survey period was 29.1 ± 9.6 days (866 observations). Mean TST of FCs was 5.7 ± 1.4 hours. In total, 32.0% of FCs were employed either full- or part-time. TST of employed FCs was significantly associated with care burden and negative affect (B = −0.4 and −1.3, respectively); however, positive affect was not associated with TST. FCs who were unemployed experienced less care burden and negative affect (rate of change: −7.7 and −8.0, respectively). Additionally, TST of unemployed FCs was associated with negative affect; thus, when they slept 1 hour longer than their mean TST, they experienced less negative affect the following day. Conclusion: A reduction in TST could lead to increased care burden and more severe negative affect the following day, which may be moderated by employment status.